2021
DOI: 10.1002/anie.202113625
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Prebiotic Formation of Nucleoside‐Amidophosphates and Nucleoside‐Triphosphates Potentiates Transition from Abiotic to Biotic Polymerization

Abstract: Polymerization of nucleic acids in biology utilizes 5'nucleoside triphosphates (NTPs) as substrates.T he prebiotic availability of NTPs has been unresolved and other derivatives of nucleoside-monophosphates (NMPs) have been studied. However,t his latter approach necessitates ac hange in chemistries when transitioning to biology.H erein we show that diamidophosphate (DAP), in ao ne-pot amidophosphorylation-hydrolysis setting converts NMPs into the corresponding NTPs via 5'-nucleoside amidophosphates (NaPs). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The excellent conversion at −20 °C was consistent with our previous results indicating that the eutectic concentrating environment of water-ice enabled efficient formation of ribonucleoside 2′,3′-cyclophosphate from the corresponding ribonucleoside 3′-monophosphates (3′-NMPs) in the presence of DAP, MgCl 2 and imidazole. 31 We attribute this significantly higher yield observed at −20 °C to (a) the freeze concentration effect 32 in co-existing water-ice phases, an effect seen in other contexts 27,33 and (b) a much slower hydrolytic degradation of DAP (when compared to room temperature and 45 °C), which allows the DAP to be available for the phosphorylation reaction over a longer period of time (see ESI Fig. S26–S31† for details).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The excellent conversion at −20 °C was consistent with our previous results indicating that the eutectic concentrating environment of water-ice enabled efficient formation of ribonucleoside 2′,3′-cyclophosphate from the corresponding ribonucleoside 3′-monophosphates (3′-NMPs) in the presence of DAP, MgCl 2 and imidazole. 31 We attribute this significantly higher yield observed at −20 °C to (a) the freeze concentration effect 32 in co-existing water-ice phases, an effect seen in other contexts 27,33 and (b) a much slower hydrolytic degradation of DAP (when compared to room temperature and 45 °C), which allows the DAP to be available for the phosphorylation reaction over a longer period of time (see ESI Fig. S26–S31† for details).…”
Section: Resultsmentioning
confidence: 97%
“…26 Recently, we showed that DAP enables the conversion of 5 ′ -NMPs and 5 ′ -oligonucleotide monophosphates into the corresponding nucleoside triphosphates (5 ′ -NTPs) and 5 ′ -oligonucleotide triphosphates via amidophosphates in a one-pot amidophosphorylation-hydrolysis setting in water. 27 Inspired by these observations, we reasoned that phosphopeptides might also undergo a similar amidophosphorylation-hydrolysis to afford the corresponding pyrophosphopeptides in one-pot, 28,29 considering the plausible reactive groups in the side chains (e.g., lysine, aspartate, glutamate, cysteine, etc. ).…”
Section: Resultsmentioning
confidence: 99%
“…Such diversions from the immediate thermodynamic and kinetic fates are critical for life and seen throughout the metabolism, certainly in biochemical pathways. While numerous reports have proven the possibility of prebiotic synthesis of nucleotides (ref and the references therein, refs and ), the eventual fate of these prebiotic nucleotides, in the absence of a primordial catalyst or a binder that stabilizes the ground states, would be nucleosides plus phosphates (black curved arrows in Figure , panel B). In such a scenario, primordial phosphate-binding polypeptides could channel ADP molecules to be converted into ATP and AMP (Figure A, B; red curved arrows in Figure , panel B), thus diverting the reaction’s eventual outcome (adenosines and phosphates).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the nucleoside Barbitudine is an interesting candidate as a prebiotic genetic alphabet to study early RNA evolution. Additionally, Krishnamurthy 42 and Powner 43 groups recently explored the route for the prebiotic formation of nucleoside triphosphates, as these are thought to have paved the way from abiotic to biotic transition. Given all these aforementioned studies, we felt encouraged to synthesize Barbitudine triphosphate ( BaTP ), and systematically explore it as a putative pre-RNA World prebiotic genetic alphabet.…”
Section: Mainmentioning
confidence: 99%